Toward a global harmonization of service infrastructure in academic clinical trial units: an international survey - Hoffmann, Jean-Marc; Blümle, Anette; Grossmann, Regina; Yau, Henry; Lang, Britta; Bradbury, Cedric (Frontiers in Medicine, 2023)
Background: Clinicians around the world perform clinical research in addition to their high workload. To meet the demands of high quality Investigator Initiated Trials (IITs), Clinical Trial Units (CTUs) (as part of Academic Research Institutions) are implemented worldwide. CTUs increasingly hold a key position in facilitating the international mutual acceptance of clinical research data by promoting clinical research practices and infrastructure according to international standards. Aim: In this project, we aimed to identify services that established and internationally operating CTUs – members of the International Clinical Trial Center Network (ICN) – consider most important to ensure the smooth processing of a clinical trial while meeting international standards. We thereby aim to drive international harmonization by providing emerging and growing CTUs with a resource for informed service range set-up. Methods: Following the AMEE Guide, we developed a questionnaire, addressing the perceived importance of different CTU services. Survey participants were senior representatives of CTUs and part of the ICN with long-term experience in their field and institution. Results: Services concerning quality and coordination of a research project were considered to be most essential, i.e., Quality management, Monitoring and Project management, followed by Regulatory & Legal affairs, Education & Training, and Data management. Operative services for conducting a research project, i.e., Study Nurse with patient contact and Study Nurse without patient contact, were considered to be least important. Conclusion: To balance the range of services offered while meeting high international standards of clinical research, emerging CTUs should focus on offering (quality) management services and expertise in regulatory and legal affairs. Additionally, education and training services are required to ensure clinicians are well trained on GCP and legislation. CTUs should evaluate whether the expertise and resources are available to offer operative services.